DNA Barcoding: A Study of Guppy Fish (Poecilia reticulata) in East Java, Indonesia - Sucipto Hariyanto; Hasan Adro’i; Mahrus Ali; Bambang Irawan (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Poecilia reticulata is a freshwater fish from the northeastern part of South America and spread widely to various countries in Asia and other continents. However, research about P. reticulate is limited even though it is a well-known fish species in Indonesia. The purpose of study was to identify the fish species of P. reticulata through DNA barcoding using the COI gene to determine the phylogenetic relationships among fish populations in East Java, Indonesia. In a present study, there were eight samples of P. reticulata from four different freshwater locations in East Java. Extraction, amplification, and sequencing of DNA samples were conducted to obtain the genetic data and construct a phylogenetic tree based on DNA sequences. The COI gene is the most popular markers to study genetic populations and phylogeography among the animal kingdom. Our phylogenetic reconstruction showed a clear that there were two groups of P. reticulata. The first group was obtain through species from East Java, Sukabumi, West Java (KU692776.1), Dominican Republic, Pandeglang, Banten and Myanmar. The second group was P. reticulata from southern Africa, Brazil, and Sukabumi, West Java (KU692775.1). The result of this study indicate that the guppy fish in East Java identic with P. reticulata from West Java (KU692776.1), which a widely used in classification based on evolutionary relationships. The findings of this study have important implication for the development of advance research about adaptation, phylogeny, and evolution of fish, especially of guppy fish.